A Case of Polycystic Ovarian Syndrome Resolved by Pulsatilla (Advancements in Homeopathic Research, 2023)
Polycystic ovarian syndrome (PCOS) is one of  the most common hormonal disorders among  women of reproductive age and a leading cause  of female infertility. A case successfully treated  by homoeopathy is presented here to acquaint the  homoeopathic physicians about the efficacy of  homoeopathic medicine selected on individualistic  basis in the treatment of PCOS.
Keywords: Constitutional medicine; holistic; homoeopathy; polycystic ovarian syndrome; Pulsatilla; ultrasonography